The Centrality of Events, Religion, Spirituality, and Subjective Well-Being in Latin American Jewish Immigrants in Israel - Simkin, Hugo (Frontiers in Psychology, 2020)
This study aims to explore the impact of migration as a central event in personal identity, spirituality, and religiousness on subjective well-being (SWB). The sample was composed of 204 Latin American immigrants living in Israel, with ages ranging from 18 to 80 years (M = 48.76; SD = 15.36) across both sexes (Men = 34.8%; Women = 65.2%). The results show that, when analyzing the effects on SWB, Positive and Negative Affect, Centrality of Event, Religious Crisis, and Spiritual Transcendence present as the most relevant explanatory variables within the models. However, contrary to expectation, the present study identifies positive associations between the centrality of migration and SWB. Motivations for emigration should be explored in further studies as they could be mediating the relationship between centrality of events and SWB.